2005
DOI: 10.1051/0004-6361:20042316
|View full text |Cite
|
Sign up to set email alerts
|

The radio counter-jet of the QSO 3C 48

Abstract: Abstract. We present multi-frequency radio observational results of the quasar 3C 48. The observations were carried out with the Very Large Array (VLA) at five frequencies, 0.33, 1.5, 4.8, 8.4, and 22.5 GHz, and with the Multi-Element Radio Linked Interferometer Network (MERLIN) at the two frequencies of 1.6 and 5 GHz. The source shows a one-sided jet to the north within 1 , which then extends to the northeast and becomes diffuse. Two bright components (N2 and N3), containing most of the flux density, are pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…This is identical with the radio position of the QSO (e.g., Feng et al 2005). The total on-source integration time was ∼6.5 h. Although the 1.2 mm receiver was tuned to the redshifted frequency of 13 CO(3-2), no 1.2 mm line signal was detected to a flux limit of 3.4 Jy km s −1 over the same velocity range of −220 to +160 km s −1 where the CO(1-0) is observed.…”
Section: Observationssupporting
confidence: 71%
See 1 more Smart Citation
“…This is identical with the radio position of the QSO (e.g., Feng et al 2005). The total on-source integration time was ∼6.5 h. Although the 1.2 mm receiver was tuned to the redshifted frequency of 13 CO(3-2), no 1.2 mm line signal was detected to a flux limit of 3.4 Jy km s −1 over the same velocity range of −220 to +160 km s −1 where the CO(1-0) is observed.…”
Section: Observationssupporting
confidence: 71%
“…The two nuclear components are not resolved but the peak flux of 230 mJy/beam is lower than the integrated flux density of 270 mJy, so the continuum is not a single point source. This is also evident from the cm-radio maps and spectra published by Feng et al 2005. Most of the (cm-)radio continuum flux comes from the radio jet and/or the northeast component 3C 48A.…”
Section: The 35 MM Continuummentioning
confidence: 60%
“…These images are shown in Figure 4, along with the location in the line profile each represents. We also show the radio jet (Feng et al 2005) at the same scale.…”
Section: The Distribution Of Extended Emission In the Nuclear Regionmentioning
confidence: 86%
“…The number in the upper left corner of the images gives the central velocity shift of the image, in km s À1 in the quasar frame, from the systemic redshift of 0.36933. The 5 GHz Merlin radio contours from Feng et al (2005) are shown superposed on the image near the peak of the high-velocity system in the lower right panel. All images use a common intensity mapping and have north up and east to the left.…”
Section: The Distribution Of Extended Emission In the Nuclear Regionmentioning
confidence: 99%
“…This might result from a projection on the plane of the sky of a helically twisted jet. Helical jets could be triggered by periodic variation in the direction of jet ejection (Linfield 1981;Stirling et al 2003;Zhao et al 2011), Kelvin-Helmboltz instabilities in the jet flow (Hardee 2003;Feng et al 2005;An et al 2010), or the magneto-hydrodynamics of the jet (Camenzind 1986) and can result in quasi-periodic flux density variability (Camenzind & Krockenberger 1992;An et al 2013;Wang et al 2014;Mohan & Mangalam 2015). The 15-GHz VLBA monitoring observation inferred superluminal motions of two jet components from 14-epoch datasets between 1995 and 2010, with a proper motion of 148 ± 15 µas yr −1 (10.1 c) at about 7 mas and 36 ± 13 µas yr −1 (2.47 c) at about 1.5 mas from the core (Lister et al 2013).…”
Section: +319 (J0205+3212)mentioning
confidence: 99%